Religiosity Level Related to Premarital Sexual Modeling in Students - Rias Pratiwi Safitri; Ni Putu Ariyani; Ana Layla Sarfarina; Harlina Putri Rusiana; Sisca Maulida Agustini (LPPM STIKES KENDAL, 2021)
Premarital sex behavior is a social phenomenon that is increasingly occurring in society. Several studies on sexual behavior reveal the rate at which sex was first performed at a young age, around high school age or at the beginning of college with an age range of 16 to 18 (Rahardjo, W., & Salve, H. R, 2014). In 2010, there were 158 countries with the minimum legal age for women to marry was 18 years and over; however, in Indonesia, the minimum age limit for women is 16 years. According to the Indonesian Student Reproductive Health Survey in Sarwono (2011), there are three factors significantly affect the students to have sexual relations, including: 1) the influence of peers or having a boyfriend, 2) having friends who agree with premarital sex, and 3) having friends who encouragepremarital sex. Modeling can be the basis for a person in certain behaviors, one of which is premarital sexual behavior. Current research was done aimed to determine the relationship between the level of religiosity and modeling of premarital sexual behavior among students in Mataram City. The research used correlation design through cross-sectional technique. The total sample of this study was 90 students. The sampling technique used was purposive sampling. This research was conducted in the Mataram City, in which the data were collected using religiosity questionnaire (modification of Hidayat, Alimul, A, A. 2012) with validity of 0.361 > 0.497-0.956 and reliability of r alpha (5%) <0.926 (significant). Premarital Sexual Modeling Questionnaire was also used (modified from Stewart & Cash, 2011) with a validity of 0.576> 0.658-0.820 and the reliability of r alpha (5%) <0.932 (significant). Based on the analysis using the Sperman rank correlation, the results obtained a significance value of (2-tailed) 0.03> 0.05. It can be concluded that Ha is accepted that there is a significant relationship between the level of religiosity with the modeling of premarital sexual behavior among students in Mataram City.